2009
DOI: 10.1038/sj.bjc.6604986
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation-mediated reduction of WWOX expression in intraductal papillary mucinous neoplasms of the pancreas

Abstract: We have previously shown that WW domain-containing oxidoreductase (WWOX) has tumour-suppressing effects and that its expression is frequently reduced in pancreatic carcinoma. In this study, we examined WWOX expression in intraductal papillary mucinous neoplasm of the pancreas (IPMN) to assess the function of WWOX in pancreatic duct tumourigenesis using immunohistochemistry and methylation-specific polymerase chain reaction analysis. Among 41 IPMNs including intraductal papillary mucinous adenomas (IPMAs) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…Leukemia is an oligoclonal or monoclonal disease, and its molecular basis remains poorly understood. The WWOX gene was previously identified from chromosome region 16q23.3-24.1 which spans the common fragile site FRA16D (1), and low expression of WWOX has also been reported in various types of cancer (5)(6)(7)(8)(9). The present study also showed that expression of WWOX (mRNA and protein) was frequently reduced or lost in different types of primary leukemia patients and cell lines, but exhibited a high expression level in healthy volunteers.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Leukemia is an oligoclonal or monoclonal disease, and its molecular basis remains poorly understood. The WWOX gene was previously identified from chromosome region 16q23.3-24.1 which spans the common fragile site FRA16D (1), and low expression of WWOX has also been reported in various types of cancer (5)(6)(7)(8)(9). The present study also showed that expression of WWOX (mRNA and protein) was frequently reduced or lost in different types of primary leukemia patients and cell lines, but exhibited a high expression level in healthy volunteers.…”
Section: Discussionsupporting
confidence: 57%
“…The present study also showed that expression of WWOX (mRNA and protein) was frequently reduced or lost in different types of primary leukemia patients and cell lines, but exhibited a high expression level in healthy volunteers. Recent evidence suggests that loss of heterozygosity, as well as epigenetic modification of the promoter by methylation, can reduce WWOX expression in various types of tumor (7,23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WWOX is a tumor suppressor gene that maps to the common fragile site FRA16D and is involved in carcinogenesis and cancer progression in a number of carcinoma types (1,19,20). The bulk of the data documented have shown that the expression of WWOX/WWOX was lost or reduced in various types of solid cancers (2)(3)(4)(5)(6)(7)(8)(9)(10). Similarly, the aberration or absence of WWOX/WWOX expression in primary hematopoietic malignancies has also been reported (11)(12)(13)(14)(15)(16).…”
Section: A B Cmentioning
confidence: 99%
“…The WWOX gene maps at the 16p23.3-24.1 chromosomal region and spans the second most common fragile site in the human genome, FRA16D (1). Since its discovery, WWOX/WWOX has been shown to exhibit reduced or no expression in a range of neoplastic diseases of varying locations, such as the lungs, breasts, bladder, ovaries, esophagus and pancreas (2)(3)(4)(5)(6)(7). Moreover, abnormal WWOX/WWOX expression profiles had been reported to be associated with a poor prognosis in carcinomas (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%